2022
DOI: 10.1590/1678-5150-pvb-6875
|View full text |Cite
|
Sign up to set email alerts
|

Ocurrence enzootic hematuria in buffaloes in Brazil: epidemiological, clinical, and pathological aspects

Abstract: It is reported the occurrence of enzootic hematuria (EH) in buffaloes in Brazil after performing an epidemiological survey and clinicopathological analises. To date, EH caused by ingestion of Pteridium esculentum subsp. arachnoideum, a radiomimetic plant popularly known as “bracken fern”, has not been described in this species in Brazil. Bovine EH is responsible for high economic losses in Brazil’s Southeast Region not only because of the deaths it causes, but also owing to its negative effect on productivity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Hemangiosarcoma, hemangioma, transitional cell carcinoma and chronic cystitis have been diagnosed in ruminant's urinary bladder secondary to braken fern ( Pteridium aquilinum ) ingestion. A study has described concomitant enzootic haematuria with gravid uterus in three buffaloes, but no alterations have been reported in the reproductive system 10,11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemangiosarcoma, hemangioma, transitional cell carcinoma and chronic cystitis have been diagnosed in ruminant's urinary bladder secondary to braken fern ( Pteridium aquilinum ) ingestion. A study has described concomitant enzootic haematuria with gravid uterus in three buffaloes, but no alterations have been reported in the reproductive system 10,11 …”
Section: Discussionmentioning
confidence: 99%
“…A study has described concomitant enzootic haematuria with gravid uterus in three buffaloes, but no alterations have been reported in the reproductive system. 10,11 This study reports the macroscopic and microscopic characteristics of uterine hemangiosarcoma in a cow referred to the veterinary hospital situated in the School of Veterinary Medicine and Animal Sciences (FMVZ) at Sao Paulo State University (UNESP). To the best of our knowledge, this is the first report of a Girolando uterine hemangiosarcoma.…”
Section: Learning Points/take-home Messagesmentioning
confidence: 99%
“…The ptaquiloside is a norsesquiterpenoid glycoside present in several fern species. The ferns most frequently linked to toxicity in South America are species of the Pteridium complex, mainly Pteridium arachnoideum and Pteridium caudatum ( Furlan et al, 2014a ; Rocha et al, 2022 ). However, recent reports demonstrated that other fern species, such as Pteris deflexa , Pteris plumula and Adiantopsis chlorophylla induce toxicity similar to that of Pteridium spp.…”
Section: Poisonous Plants In South Americamentioning
confidence: 99%